Energy Efficient Homes: Air Conditioning - Wendell A. Porter; Hyun-Jeong Lee; Kathleen C. Ruppert (EDIS, 2008)
FCS-3262, a 6-page fact sheet by Wendell A. Porter, Hyun-Jeong Lee, and Kathleen C. Ruppert, uses a question and answer format to answer homeowner questions about air conditioning and saving energy in the home. Includes references. Published by the UF Department of Family Youth and Community Sciences and Florida Energy Extension, April 22, 2008.